Producing the Self-Regulating Subject: Liberal Protection in Indonesia's Migration Infrastructure - Chang, Andy Scott (Pacific affairs, 2018)
Labour protection has become a dominant agenda in global migration governance, particularly for sending countries whose diasporic citizens are denied political rights in host states. Despite having limited authority to arbitrate extraterritorial disputes, sending countries like Indonesia have deployed novel techniques of statecraft to improve migrant protection. Through the prism of the professional competence exam and pre-departure orientation seminar, this article investigates the Indonesian state's regulatory practices that focus on migrant conduct. Although outbound domestic workers are subject to a prolonged process of skill formation, other Indonesian contract workers pursue emigration upon acquiring basic legal knowledge without undergoing accreditation. While both programs are designed to inculcate migrant capabilities for self-protection, the state's professionalization of domestic workers constitutes a liberal strategy of exclusion that is predicated on their master status as "vulnerable victims" in public discourse. To understand Indonesia's increasingly mediated migration infrastructure, then, requires attention to the liberal rationality of protection that involves the transformation of migrants into self-regulating subjects.